Romania’s Euro Area accession - Comis, Marius (Journal of Management and Financial Sciences, 2025)
Eurozone integration it is still a target and a challenge for most Eastern European countries, even after twenty years from the accession to the European Union. While financial integration is viewed as an opportunity, there is an ongoing debate about its optimal form. Beyond meeting the Maastricht Criteria, which some countries comply, several critical issues arise: what is the most appropriate type of financial integration within the European Union and can the development of a Capital Markets Union and a Banking Union effectively address market fragmentation. Moreover, in the absence of suitable institutional frameworks, are these mechanisms able to overcome asymmetric shocks accommodate economic convergence and mitigate systemic risks? Euro Area needs tools like collective deposit insurance schemes (EDIS) and to increase the resources for the Single Resolution Fund (SRF) to address systemic risks more effectively. Economic convergence mechanisms are compulsory to reduce the divergence of NPLs across member states. The creation of European "safe assets," such as Sovereign Bond-Backed Securities (SBBS), seeks to mitigate the bank-sovereign doom loop.